Overconfidence Bias Pada Indeks LQ45 di Bursa Efek Indonesia - Nurmala Suci Lestari; Tiar Lina Situngkir (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The study aims to determine whether there is an effect of overconfidence bias on the Indonesia Stock Exchange for the period 2014-2023. Overconfidence bias is a behavioral anomaly that occurs in the capital market and is related to investment returns with investor capabilities, where investors will become overconfident and trade aggressively in the following period. The limited research on Behavioral Finance Macro (BFMA,) and as well as the absence of research that details the results in ten-year, five-year, and annual periods make this research interesting. The method used in the research is Vector Autoregression (VAR) with a population of all companies in the LQ45 Index for the period 2014-2023 and a sample of 15 companies that are consistently included in the LQ45 Index during the study period using weekly close price data. The research hypothesis can be answered through the estimation of the VAR model and Impulse Response Function (IRF). Consistent with the research hypothesis, there is a positive and significant relationship between return markets and trading volume. The results of the analysis using the VAR model show that there is an effect of overconfidence bias on the Indonesia Stock Exchange in the 5-year period, namely 2014-2018 and in the annual period, namely 2015, 2018 and 2021.